2011
DOI: 10.1158/0008-5472.can-10-3055
|View full text |Cite
|
Sign up to set email alerts
|

COX-2 Blockade Suppresses Gliomagenesis by Inhibiting Myeloid-Derived Suppressor Cells

Abstract: Epidemiologic studies have highlighted associations between the regular use of nonsteroidal anti-inflammatory drugs (NSAID) and reduced glioma risks in humans. Most NSAIDs function as COX-2 inhibitors that prevent production of prostaglandin E 2 (PGE 2 ). Because PGE 2 induces expansion of myeloid-derived suppressor cells (MDSC), we hypothesized that COX-2 blockade would suppress gliomagenesis by inhibiting MDSC development and accumulation in the tumor microenvironment (TME). In mouse models of glioma, treatm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
301
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(313 citation statements)
references
References 38 publications
9
301
1
2
Order By: Relevance
“…These findings suggest that celecoxib reduces the number of tumour-infiltrating CTL while enhancing their effector functions. These data are in agreement with a previous study using glioma-bearing mice where COX2 -/-mice had increasing percentages of tumour-infiltrating CD8 + CD107a + lymphocytes [19]. This may be explained by another study reporting that COX-2 activity leads to CTL senescence and this trajectory may be opposed by COX-2 inhibition, as shown by increased levels of CD28 and interleukin-2 in CD8 + T cells [18].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings suggest that celecoxib reduces the number of tumour-infiltrating CTL while enhancing their effector functions. These data are in agreement with a previous study using glioma-bearing mice where COX2 -/-mice had increasing percentages of tumour-infiltrating CD8 + CD107a + lymphocytes [19]. This may be explained by another study reporting that COX-2 activity leads to CTL senescence and this trajectory may be opposed by COX-2 inhibition, as shown by increased levels of CD28 and interleukin-2 in CD8 + T cells [18].…”
Section: Discussionsupporting
confidence: 92%
“…This effect may explain how the abrogation of COX-2 signalling reduces tumour growth in mouse models of glioma [19] and mammary cancer [20]. In light of these findings, it is appealing to study whether CD8 + T cells present in HPV-induced lesions are affected by COX-2 inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…12 As these cells are known to impair tumor immunity, different strategies have been applied to target MDSC in cancer. Several approaches are under investigation to inhibit these cells pharmacologically, including the induction of MDSC apoptosis (by gemcitabine, sunitinib, or 5-fluorouracil) [25][26][27] , the inhibition of MDSC function (with sildenafil and cyclooxygenase 2 inhibitors) 28,29 and the promotion of maturation of MDSC into nonsuppressive cells (all-trans retinoic acid, vitamin D). 30 Here, we have shown that TLR7 stimulation leads to the upregulation of maturation markers on MDSC in vitro, a finding that is in accordance with previous reports.…”
Section: E1230578-4mentioning
confidence: 99%
“…Recently, accumulating evidence has shown that a PGE2-COX-2-mediated positive feedback loop is essential for the induction of immunosuppressive factors secreted by human MDSCs 41 and that COX-2 is implicated in tumor angiogenesis, evasion of apoptosis, and induction of EMT. 42,43 Therefore, we suppressed the expression of COX-2 in TW03 and CNE1 cells using siRNAs targeting COX-2 (siCOX-2).…”
Section: Upregulation Of Cox-2 and The B-catenin/tcf4 Pathway Contribmentioning
confidence: 99%